CFD modelling and simulation of anaerobic digestion reactors for energy generation from organic wastes: A comprehensive review - Farid, Muhammad Usman; Olbert, Indiana A.; Bück, Andreas; Ghafoor, Abdul; Wu, Guangxue (Heliyon, 2025)
Anaerobic digestion (AD) has been recognized as one of the most viable options for the treatment of a wide range of waste materials. Complex structure of wastes is safely broken down to destroy pollutants and pathogens. Biogas is produced as a by-product of this process which is considered as a clean energy resource. However, provision of controlled environment for microbial activities is critical to ensure the required process efficiency. This can only be achieved with the efficient design of controlled vessels used for anaerobic digestion, termed as AD reactors. AD functions such as mixing, hydrodynamics, multiphase interaction, heat transfer, temperature distribution and bio kinetics are significantly affected by the reactor shape, design and configurations, hence making it essential to optimize the reactor design before installation at large scale. Mostly, such optimization is carried out with the help of lab scale experimentations and testing protocols which result in high costs for repeating several design experiments. Computational fluid dynamics (CFD) is an applied mathematical tool which helps to understand and predict the fluid dynamics, heat flow as well as species transport in different domains. This approach contributes to minimize the experimental costs while optimizing the reactor configurations in less time. The current review is presented to summarize and discuss the core characteristics of AD process followed by concerned CFD attributes. Research gaps and critical challenges are identified in different aspects such as reactor design, and configuration, mixing, multiphase flow, heat transfer, biokinetics as well as machine learning approache
Keywords: Anaerobic digestion; Reactor design; CFD; Hydrodynamics; Multiphase

Optimizing the design of a multi-stage tangential roller threshing unit using CFD modeling and experimental studies - Hussain, Saddam; Lei, Xingpeng; Wu, Hongqi; Li, Hao; Song, Haiyan; Zheng, Decong; Jiawei, Wang; Li, Anbang; Farid, Muhammad Usman; Ghafoor, Abdul (Computers and Electronics in Agriculture, 2024)
Rising global population of the world is resulting higher demand for buckwheat being a high-quality food crop. In this study, the multi-stage shearing drum working mode was proposed to solve the problems of easy entanglement, blockage in threshing process due to inconsistency of ripening period, decrease grain breakage rate and loss rate and increase threshing efficiency. The designed threshing unit incorporates key components: frame, feeding wheel, main and secondary threshing drums, discharge unit, and concave plate. FEA and modal analysis were integrated to assure robust structural performance and stability of the threshing components within set limits, which were validated by indoor testing that confirmed the threshing drum's working frequency did not cause resonance. Single Factor Method identifies optimal conditions: 600 rpm, 7 mm, 1.2 kg/s for minimal grain breakage; 700 rpm, 9 mm, 1.2 kg/s for lowest grain loss. A three-factor, three-level orthogonal experiment validates these findings. In conclusion, optimal results are achieved with a drum speed of 600 rpm, feeding rate of 1.2 kg/s, and a threshing gap of 9 mm thus, minimizing both grain loss and breakage rates.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Buckwheat breeding; buckwheat thresher; finite element analysis; model analysis; multi-stage threshing; RSM

Stability, convergence, and energy preservation robust methods for fully implicit and fully explicit coupling schemes - Munir, Taj; Kang, Can; Chen, Hongchu; Zeb, Hussan; Khan, Muhammad Naveed; Farid, Muhammad Usman (Chaos Solitons & Fractals, 2025)
This paper presents an analysis of the Godunov–Ryabenkii stability, Generalized Mini-mal Residual(GMRES) convergence, and energy-preserving properties of partitioned and monolithic approaches (fully implicit and fully explicit schemes) for solving coupled parabolic problems. Specifically, we consider a bi-domain parabolic diffusion problem with two types of coupling conditions at the interface: Dirichlet–Neumann and heat-flux coupling. Our findings shows that the Dirichlet–Neumann coupling is unconditionally stable for both approaches. In contrast, the heat-flux coupling requires additional conditions to ensure the stability of the coupled problem. For numerical approximations, finite volume and finite difference schemes are used. The results show that energy preservation is achieved with one-sided differences in the finite volume method, while the finite difference method achieves conservation when central difference approximations are used for both the coupling and boundary conditions in the heat-flux coupling case. Additionally, Dirichlet–Neumann coupling maintains stability and energy preservation in both methods using the one-sided approach without requiring extra conditions. However, for heat-flux coupling, an additional restriction is necessary to ensure stability. The challenge for the convergence of coupled interface problems arise due to strong domain interactions and sensitive interface conditions, like Dirichlet–Neumann or heat-flux coupling. The poor system conditioning and discretization choices can slow the rate of convergence. For this purpose we used the GMRES method. This work provides a comprehensive framework for addressing coupled parabolic diffusion problems using robust, stable, and energy-preserving numerical methods.
CRIS-Team Scopus Importer:2025-03-14
Keywords: Conjugate heat transfer; Dirichlet–Neumann algorithms; Heat flux coupling; Stability analysis and discrete energy conservation